Padrões de comportamento e escolhas de consumo do público LGBTQIAPN+ em bares e pubs da cidade de Manaus - Silva, Rafaela Nayara Pinheiro da (Brasil, 2024)
Contemporary society, marked by its cultural diversity and multiple forms of expression, witnesses the prominent role of the LGBTQIAPN Community, recognized for its significant purchasing power, the “Pink Money”, which positively impacts the Brazilian economy (SEBRAE, 2019). This segment, the target of offers, mainly in bars and pubs (Neves; Brambatti, 2019), motivated this present study. This work sought to analyze the factors that influence the behavioral patterns and consumption choices of the LBGTQIAPN+ public in bars and pubs in the city of Manaus. To achieve this, quantitative research of applied and descriptive nature was carried out. The technical procedures used were bibliographical research, field research and a survey, whose data were collected using Google Forms, involving a sample of 327 LGBTQIAPN+ respondents from the city who attend these places. The results indicate five predominant factors in consumption choices: reference groups, music, comfort, price, and physical environment. These elements not only shape consumption choices, but also directly influence social interactions and consumer behavior within these establishments, highlighting the importance of an in-depth understanding of the profile of this public.